Different no more: Country spreads in advanced and emerging economies - Benjamin Born; Gernot J. Müller; Johannes Pfeifer; Susanne Wellmann (University of Tübingen, Faculty of Economics and Social Sciences, 2020)
Interest-rate spreads fluctuate widely across time and countries. We illustrate this on the basis of about 3,100 quarterly observations for 21 advanced and 17 emerging economies since the early 1990s. Prior to the financial crisis, spread fluctuations in advanced economies are an order of magnitude smaller than in emerging economies. After 2008 their behavior has largely converged along a number of dimensions. We also provide evidence on the transmission of spread shocks and find it similar across sample periods and country groups. The importance of spread shocks as a source of output fluctuations in advanced economies has increased after 2008.
urn:nbn:de:bsz:21-dspace-974842
Keywords: G15; F41; E32; 330; Country spreads; Country risk; Interest-rate shocks; Financial crisis; Business cycle; Spread shocks; Average treatment effect